Child and adolescent psychiatry training curriculum: a global trainee's perspective. (August 2020) - Gnanavel, Sundar; Sharma, Pawan; Sebela, Antonin; Alemany, Teresa Gomez; Chang, Jane Pei-Chen; de Medeiros Filho, Mauro Victor; Kusi-Mensah, Kwabena; Kaligis, Fransiska; Kato, Hidekazu; Le, Huu Kim; Morimoto, Kana; Martsenkovskyi, Dmytro; et al.
Abstract : This article is a summary of perspectives on training curricula from child and adolescent psychiatry trainees globally. We aimed to identify the relative strengths, weaknesses and gaps in learning needs from a trainee's perspective. The 20 early-career child psychiatrists who contributed are from 16 countries and represent all the five continents. We could identify some global challenges as well as local/regional challenges that need to be addressed to develop competent child psychiatrists.